PERENCANAAN ULANG RODA GIGI PINION PADA GARDAN BELAKANG KENDARAAN ISUZU OZ - Aryananta Lufti; Edy Budi Santoso; Nurtjahyono (JURNAL MEKANIKASISTA, 2025)
Gears are one of the essential machine elements that function to transmit power and rotation accurately from one shaft to another. In the transmission system of the Isuzu OZ vehicle, the pinion gear plays an important role as the main driver in transferring power from the engine to the rear-wheel drive system. Gears are preferred over other transmission systems due to several advantages, including a more compact system, simple construction, high load-carrying capacity, high power transmission efficiency, and minimal slip occurrence. One of the most commonly used gear types in vehicle transmission systems is the bevel gear, where the pitch surface is conical, with its apex located at the intersection point of the shaft axes. Based on the shape and direction of the teeth, bevel gears are classified into four types: straight bevel, zerol bevel, spiral bevel, and hypoid bevel gears. The hypoid type is a development of the spiral bevel gear, offering higher efficiency and the ability to transmit greater torque in heavy-duty vehicles. Therefore, the selection and design of the pinion gear play a crucial role in improving the efficiency, durability, and overall performance of the Isuzu OZ vehicle transmission system.